A global approach to describe retinal defocus patterns - García García, Miguel; Pusti, Dibyendu; Wahl, Siegfried; Ohlendorf, Arne (PloS one, 2019)
The popularity of myopia treatments based on the peripheral defocus theory has risen. So far, little evidence has emerged around the questions which of these treatments are effective and why. In order to establish a framework that enables clinicians and researchers to acknowledge the possible interactions of different defocus patterns across the retina, different peripheral refractive errors (PRX) of subjects and different designs of optical treatments were evaluated. Dioptric defocus patterns on the retinal level have been obtained by merging the matrices of dioptric defocus maps of the visual field of different scenarios with individual peripheral refractive errors and different optical designs of multifocal contact lenses. The newly obtained matrices were statistically compared using a non-parametric test with familywise error algorithms and multi-comparison tests. Results show that asymmetric peripheral refractive error profiles (temporal or nasal positively skewed) appear to be less prone to be changed by the defocus imposition of multifocal contact lenses than those presenting symmetric patterns (relative peripheral myopia or hyperopia).